Effects of prescribed fire timing on yearling stocker cattle performance, native plant composition, forage biomass accumulation, and root carbohydrate concentrations in key native tallgrass plant species - Duncan, Zachary Michael (Kansas State University, 2020)
Recent research demonstrated that mid- or late-summer prescribed fire can be employed to manage sericea lespedeza infestations in the Kansas Flint Hills. Despite optimistic reports, ranchers have voiced concerns that mid- or late-summer prescribed fire may negatively affect stocker cattle growth performance, native warm-season plant populations, or forage biomass accumulation. Eighteen pastures were grouped by watershed and assigned to one of three prescribed-fire treatments: spring (7 April ± 2.1 d), summer (21 August ± 5.7 d), or fall (2 October ± 9.9 d). All prescribed fire treatments were applied prior to grazing in 2019 and 2020. Yearling beef cattle were grazed from May to August at a targeted stocking density of 279 kg live-weight ˖ ha⁻¹. Forage biomass accumulation was measured in July of 2018 and 2020 by clipping vegetation within 0.25²-meter frames. Soil cover, botanical composition, and root carbohydrate concentrations of key native tallgrass species were evaluated during the growing seasons of 2018, 2019, and 2020. After 2 complete years of prescribed fire application and grazing, total body weight gains and average daily gains were greater (P = 0.01) for cattle that grazed the spring and summer prescribed-fire treatments compared with those that grazed the fall prescribed-fire treatment. As a result, final body weights were greater (P = 0.04) in the spring and summer fire treatments compared with the fall fire treatment. Conversely, forage biomass accumulation did not differ (P = 0.91) between fire regimes. When soil cover was evaluated, proportions of bare soil were greater (P < 0.01) in the spring treatment compared with the summer and fall treatments, whereas proportions of litter on the soil surface were greater (P < 0.01) in summer- and fall-burned pastures compared with spring-burned pastures. Basal cover of all graminoids and forbs did not differ (P= 0.15) between prescribed fire treatments; however, total shrub cover tended to be greater (P = 0.08) in the summer and fall prescribed-fire treatments compared with the spring prescribed-fire treatment. Total basal cover of C4 perennial grasses and C4 tallgrasses did not differ (P ≥ 0.07) between prescribed fire treatments; however, C4 mid-grass cover was greatest (P = 0.05) in spring-burned pastures, intermediate in summer-burned pastures, and least in fall-burned pastures. Furthermore, C4 shortgrass cover was greater (P = 0.01) in the spring fire treatment compared with the summer and fall fire treatments. Conversely, basal cover of native grasses was greater (P = 0.02) in the summer fire treatment compared with the fall fire treatment, while pastures burned in the spring were intermediate to and not different from the summer and fall fire treatments. Basal cover of nectar-producing forbs was greater (P = 0.02) in the summer and fall fire regimes compared with the spring fire regime. No differences (P = 0.24) in root starch or total root water-soluble carbohydrate concentrations in big bluestem, little bluestem, Indiangrass, or purple prairieclover were observed between prescribed fire treatments. These data were interpreted to suggest that summer or fall prescribed fire can be applied without reducing forage biomass accumulation, root carbohydrate concentrations of key tallgrass species, or considerably altering native plant populations; however, summer prescribed fire could be favored over fall prescribed fire to maintain stocker cattle growth performance.
Keywords: Grazing; Prescribed fire; Sericea lespedeza